PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DELFI HOT COCOA DI SUPERMARKET MAJU BERSAMA GLUGUR MEDAN - Wijaya, Muslim (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
This research intends to know is the price influence to the buyer decision Delfi Hot Cocoa of Maju Bersama Departement Store Medan, (2) Is the product quality influence on the buyer decision Delfi Hot Cocoa of maju Bersama Department store Medan. Simultanly this research head for knowing the influence of price andÂ  product quality to the buyer decision of Maju Bersama Department store Medan. The population of the these research are 120 consumer who eat the delfi hot cocoa of Maju Bersama Departement Stor Medan and the sample are 92 consumer who eat the Delfi Hot Cocoa od Maju Bersama Departement Store. Keywords: Price, Quality Of Product, Buyer Decision